A High Performance Liquid Chromatographic Assay for Mosapride Citrate - KRISHNAIAH, Y.S.R.; MURTHY, T.K.; SANKAR, D.G.; SATYANARAYANA, V. (Asian Journal of Chemistry, 2010)
A rapid and sensitive reverse phase high performance liquid chromatographic method has been described for the estimation of mosapride citrate in bulk drug samples and pharmaceutical dosage forms using RP C-18 column. Nifedipine was used as internal standard. The mobile phase consisted of methanol and water in the ratio of 73 : 27 respectively, and was pumped at 1.3 mL/min at 40oC. The drug and internal standard were eluted at 4.11 min and 2.54 min respectively. The detection was carried out at 274nm and the calibration curve was linear in the range of 0.01 to 20 μg/mL. The method was statistically validated for its linearity, precision and accuracy. The intra- and inter-day variation was found to be less than 1 % showing high precision of the assay method. The detection limit was found to be 5 μg/mL. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining mosapride citrate in bulk drug samples or in pharmaceutical formulations.